2019
DOI: 10.1136/bmjopen-2018-027473
|View full text |Cite
|
Sign up to set email alerts
|

The James Lind Alliance process approach: scoping review

Abstract: ObjectiveTo summarise study descriptions of the James Lind Alliance (JLA) approach to the priority setting partnership (PSP) process and how this process is used to identify uncertainties and to develop lists of top 10 priorities.DesignScoping review.Data sourcesThe Embase, Medline (Ovid), PubMed, CINAHL and the Cochrane Library as of October 2018.Study selectionAll studies reporting the use of JLA process steps and the development of a list of top 10 priorities, with adult participants aged 18 years.Data extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 45 publications
(422 reference statements)
1
63
0
1
Order By: Relevance
“…It is highly likely that we did not reach the weakest voices when conducting this process, i.e. individuals in low socioeconomic groups, with low health literacy or who have no access to the internet and social media (8). Consideration should be given to identifying submissions from the service users separately if conducting a similar process in a larger project.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is highly likely that we did not reach the weakest voices when conducting this process, i.e. individuals in low socioeconomic groups, with low health literacy or who have no access to the internet and social media (8). Consideration should be given to identifying submissions from the service users separately if conducting a similar process in a larger project.…”
Section: Discussionmentioning
confidence: 99%
“…There are probably as many approaches to user involvement in research prioritisation as there are priority-setting exercises, and a gold standard is therefore not attainable, nor is it appropriate (7). The James Lind Alliance process focuses on bringing together service users, next of kin and clinicians, also referred to as stakeholders, on equal terms to explore research priorities in a priority-setting partnership (8), and the framework was found t for the purpose as inspiration (7,9). Although PPI is applied in many studies, detailed descriptions of the process of involving participants/stakeholders are still lacking (4,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Moreover, the refinement of raw research suggestions into a shortlist of ''indicative'' research questions is a subjective process that often involves rewording of questions, amalgamation of similar themes, the finer details of which have been shown to vary significantly between different PSPs. 10 While the CAR PSP appears to have followed the JLA methodological principles in reducing a list of 500? suggestions into a manageable shortlist of 49, this area of JLA methodology clearly requires further scrutiny.…”
mentioning
confidence: 99%
“…9 Qui plus est, le peaufinage de suggestions de recherche brutes en une présélection de questions de recherche « indicatives » est un processus subjectif qui implique souvent de réécrire les questions, d'amalgamer des thèmes semblables, et il a été démontré que cela peut varier beaucoup d'un PSP à l'autre. 10 Bien que le CAR PSP semble avoir respecté les principes méthodologiques de la JLA en réduisant une liste de plus également un débat approfondi sur le rôle de la recherche axée sur le patient en anesthésie et en médecine périopératoire. Alors que la plupart d'entre nous sommes d'accord que l'un des buts ultimes de la recherche en anesthésie est d'améliorer les devenirs des patients, le temps et l'énergie des patients et du grand public ne sont pas infinis.…”
unclassified